Is hepatocellular carcinoma complicated with portal vein tumor thrombosis potentially curable by radiotherapy in the form of stereotactic body radiation therapy?. (3rd October 2022) - Srivastava, Astha; Parambath, Haresh Kunhi; Ramdulari, Anjali V.; Saxena, Harsh; Kumar, Rishabh; Pandey, Suyash; Shalimar; Gupta, Subhash; Jee, Babban
Abstract: Purpose: The prognosis of hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) is dismal. Despite best treatment and care, the patients with this malignancy only showed 2.7–4 months of overall survival. It is debatable whether liver transplantation helps PVTT sufferers. The effectiveness of radiation therapy in treating HCC patients with PVTT should not be undervalued. By limiting the high dosage region to a small planning target volume, stereotactic radiation delivery has shifted toward hypofractionation, limiting the radiation exposure to healthy organs and tissues. Stereotactic body radiotherapy (SBRT) has a local control rate of 75–100%, depending on the treatment. The major limitation in SBRT for hepatocellular carcinoma with PVTT is the paucity of prospective evidence for longer periods beyond the first two years after treatment. More prospective studies/randomized clinical trials with a longer follow-up, larger sample size, and adequate statistical power are the dire need of the present situation to ascertain the curative effect of SBRT as primary therapy for advanced HCC with PVTT. Conclusion: SBRT can improve survival, particularly for patients receiving multidisciplinary treatment. This review sums up our most current understanding of how radiation therapy, notably SBRT, can be used to treat hepatocellular carcinoma when combined with PVTT. Recent research has led us to believe that irradiation in the form of SBRT may cure hepatocellular carcinoma complicated by PVTT.